John Steinbeck : the Real(ist) Gothic? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, New Zealand - Stephenson, Joanna (Massey University, 2020)
There is a wealth of existing scholarship that firmly locates John Steinbeck’s fiction in the school of Realism. Yet, the tenets of the Gothic mode can be applied to several motifs encased in Steinbeck’s significant Depression-era texts The Grapes of Wrath, Of Mice and Men, and The Pastures of Heaven. Notably, Steinbeck employs the Gothic when demonstrating monstrosity in the increasingly modernised world, and the tension amongst marginalised groups. The national mythology of the American Dream is steadily eroding in the Thirties and transforming into a Gothic nightmare, which is telegraphed in these novels by depictions of death, violence, hopelessness, and curses. Modernity is encroaching on the American pastoral, which Steinbeck illustrates by Gothicising agricultural processes and representing machines in monstrous terms. Steinbeck’s fiction evokes the suspense and hostility of the Southern Gothic tradition with his portrayal of alienated individuals and intolerant communities.
Keywords: 470523 North American literature